Gender Differences in Scholarly Productivity Within Academic Gynecologic Oncology Departments. Issue 6 (December 2015) - Hill, Emily K.; Blake, Rachel A.; Emerson, Jenna B.; Svider, Peter; Eloy, Jean Anderson; Raker, Christina; Robison, Katina; Stuckey, Ashley
Abstract : OBJECTIVE: To estimate whether there is a gender difference in scholarly productivity among academic gynecologic oncologists. METHODS: In this cross-sectional study, the academic rank and gender of gynecologic oncology faculty in the United States were determined from online residency and fellowship directories and departmental web sites. Each individual's h-index and years of publication were determined from Scopus (a citation database of peer-reviewed literature). The h-index is a quantification of an author's scholarly productivity that combines the number of publications with the number of times the publications have been cited. We generated descriptive statistics and compared rank, gender, and productivity scores. RESULTS: Five hundred seven academic faculty within 137 U.S. teaching programs were identified. Of these, 215 (42%) were female and 292 (58%) were male. Men had significantly higher median h-indices than women, 16 compared with 8, respectively ( P <.001). Women were more likely to be of junior academic rank with 63% of assistant professors being female compared with 20% of full professors. When stratifying h-indices by gender and academic rank, men had significantly higher h-indices at the assistant professor level (7 compared with 5, P <.001); however, this difference disappeared at the higher ranks. Stratifying by the years of active publication, there was no significant difference between genders. CONCLUSION: Female gynecologic oncologists at the assistant professor level had lower scholarly productivity than men; however, at higher academic ranks, they equaled their male counterparts. Women were more junior in rank, had published for fewer years, and were underrepresented in leadership positions. LEVEL OF EVIDENCE: III Abstract : Although women in academic gynecologic oncology at the assistant professor level have lower scholarly productivity than men, this difference disappears at higher academic ranks.